Risk and reliability : coastal and hydraulic engineering - Reeve, Dominic (Spon Press, 2009)
Sets out the methods which are increasingly being required by government agencies for river and sea defence design and flood defence system management. It highlights the major concepts developed during the last two decades for describing uncertainty in the performance of flood and erosion defences. It begins with an introduction to the key statistical concepts required for the implementation of a reliability analysis: both the analytical and the numerical methods used in this are described with worked examples.